(untitled) (Journal of the College of Basic Education, 2023)
Winston Churchill is one of the political leaders and prime minister of Britain and one of the greatest personalities that appeared in British history. At the beginning of his first life as an officer in the British army, in addition to being a writer, historian and artist at the same time, and he won the Nobel Prize in Literature, he held many political and governmental positions in Britain, where he headed the Ministry of Industry and Trade, the Ministry of the Interior, and became the British Minister of the Navy.He stood in the face of German Nazism and its leader, Hitler, who worked to rearm Germany and in World War II. He participated in all conferences that contributed to the defeat of the Axis powers and the establishment of the United Nations Organization in 1945. After the end of the war, Churchill resigned from his position, but he returned and became prime minister during the years 1951-1955 Even after his resignation from the position, he remained a member of the British House of Commons until 1964, when in his last years he suffered strokes and died in 1965.